2013
DOI: 10.1108/s0147-9121(2013)0000037007
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship of the Left-Behind

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…For example, Biavaschi et al (2015) found that being left-behind triggers a stronger influence of older siblings on the schooling performance of the youngest. On the other hand, Giulietti et al (2013) found that left-behind individuals are less likely to be selfemployed when compared to return migrants and individuals who live in non-migrant households. Since these factors are already controlled for in the regression, we interpret the negative estimate as the psychological cost associated with the migrant's absence (albeit often temporary).…”
mentioning
confidence: 91%
“…For example, Biavaschi et al (2015) found that being left-behind triggers a stronger influence of older siblings on the schooling performance of the youngest. On the other hand, Giulietti et al (2013) found that left-behind individuals are less likely to be selfemployed when compared to return migrants and individuals who live in non-migrant households. Since these factors are already controlled for in the regression, we interpret the negative estimate as the psychological cost associated with the migrant's absence (albeit often temporary).…”
mentioning
confidence: 91%
“…Also for China, Giulietti et al (2013) find that not only return migrants are more likely than non-migrants to start up a business but also they promote entrepreneurship amongst family members who did not migrate, suggesting that knowledge and experience may be skills required in China's rural areas to stimulate entrepreneurship. Wahba and Zenou (2012), using migration data from Egypt, also find that experience, savings and duration abroad matter and that the loss of social capital due to being out of the country does not outweigh the benefits of finance and experiences in starting up a firm.…”
Section: Are Return Migrants More Likely To Be Entrepreneurial Than Nmentioning
confidence: 99%
“…De même, les migrants de retour peuvent utiliser les économies qu'ils ont accumulées à l'étranger pour se mettre à leur compte. De plus en plus d'études montrent que les migrants de retour et les membres de leur ménage ont tendance à être des travailleurs indépendants ou à créer leur propre entreprise (Ammassari, 2004 ;Giulietti et al, 2013).…”
Section: Les Transferts De Fonds Et La Migration De Retour Favorisentunclassified